PENGARUH KUALITAS PELAYANAN DAN BRAND EQUITY PEGADAIAN SYARIAH DIGITAL TERHADAP KEPUASAN NASABAH - Dyah Pikanthi Diwanti; Linda Anindita (Ekonomi Islam, 2020)
The purpose of this study was to determine the effect of service quality variables (X1) and brand equity (X2) of digital sharia pawnshops on customer satisfaction in Yogyakarta sharia pawnshops. The research data collecting was through questionnaire method which was distributed to 42 pawnshop customers using purpose sampling method. The quantitative analysis includes validity, reliability test, classical assumption test including normality test, hetoroscedasticity test, multicollinearity test. The hypothesis testing was through T test and simultaneous test. The results of this study show that service quality has a significant positive effect on customer satisfaction with the value of t = 1.796. Brand Equity has a significant positive effect on customer satisfaction with the value of t = 2.956. The results simultaneously show the magnitude of the F value with a significance of 0,000 <0.05, so it can be concluded that simultaneously service quality and brand equity variables affect customer satisfaction variables.